2005
DOI: 10.1177/107179190501200108
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Pre-Employment Expectations, Experiences, and Length of Stay in Public Accounting

Abstract: This study examines the relationship between work-family conflict, employment expectations, and length of stay in public accounting. Length of stay is modeled as a function of demographic factors and job characteristics associated with work-family balance, measured in terms of the extent to which the employees' expectations matched their actual employment experiences. Results indicated that gender, the presence of children in the household, flexible schedules, and the presence of mentors were related to length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…While many studies (Almer & Kaplan, 2002;Padgett, et al, 2005) have focused on the work schedule needs of professional accountants, the preferences of students have not been analyzed. This study's results provide important insights into the nature of schedule preferences for not just post-graduation employment but also for pre-graduation student internships.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While many studies (Almer & Kaplan, 2002;Padgett, et al, 2005) have focused on the work schedule needs of professional accountants, the preferences of students have not been analyzed. This study's results provide important insights into the nature of schedule preferences for not just post-graduation employment but also for pre-graduation student internships.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-employment expectations that do not match the reality of the job can lead to low job satisfaction and low organizational commitment. These are the two most direct antecedents of the decision to leave an accounting firm (Padgett et al, 2005). Some research has indicated that the expectations prior to accepting a job can be more important than the actual experiences an employee has on the job (Padgett et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations